Demand‐avoid‐withdraw processes in adolescent dating aggression. Issue 3 (16th January 2023) - Lorber, Michael F.; Mitnick, Danielle M.; Tiberio, Stacey S.; Heyman, Richard E.; Slep, Amy M. S.; Trindade, Samara; Damewood, Gabriella N.; Bruzzese, Jean‐Marie
Abstract: We conducted an observational study of a collection of interactive processes known as "demand‐withdraw" in relation to adolescent dating aggression. Couples ( N  = 209) aged 14–18 years participated in a challenging observational laboratory assessment to measure demands (i.e., pressures for a change), as well as demand → partner withdraw and demand → partner avoid sequences. Actor and partner effects were disentangled via dyadic data analyses. The results indicated a fairly consistent pattern in which demand → withdraw and demand → avoid sequences led by either partner were positively associated with both partners' physical and psychological aggression (measured via a dual informant questionnaire method). Further, higher quality demands (i.e., pressures for change that were specific and encouraged both members of the dyad to increase a given behavior) were inversely associated with aggression. Yet, all of the above associations were attenuated to the point of statistical nonsignificance after controlling for hostility. These results suggest two primary possibilities. The associations of demand → withdraw and demand → avoid sequences with dating aggression may be spurious, with the sequences merely markers for hostility, a known correlate of dating aggression. Alternatively, hostility may mediate the relations of demand → withdraw and demand → avoid sequences with dating aggression. Further research is required to test these competing explanations. Implications for preventive intervention are discussed.